Fine structure of the cottontail rabbit papillomavirus mRNAs expressed in the transplantable VX2 carcinoma. - Danos, O (1985)
We analyzed the polyadenylated mRNAs transcribed from the cottontail rabbit papillomavirus genomes present in the domestic rabbit transplantable carcinoma line VX2, employing a combination of S1 nuclease mapping and primer extension techniques with vector M13-based single-stranded DNA probes. Each of the two major mRNA species (1,860 and 1,110 bases long) contained two exons which corresponded to the E6-E7 and E2-E4 open reading frames. The splice donor site for these transcripts was located at position 1371 at the beginning of the E1 open reading frame. Consequently, the splicing event did not lead to the fusion of the E region proximal (E6 and E7) and distal (E2, E4, or E5) open reading frames. The translation of the polycistronic RNA could result in the production of E6 and E7 proteins alone or of an additional E1-E4 fusion product if translation reinitiation can occur after the E7 stop codon. A heterogeneity was detected in the 5' ends of the longer transcript; E6 transcripts could thus yield a full-length or a truncated E6 protein. We also detected a minor subset of mRNAs covering the E2-E4 coding region and including at least three species with estimated sizes of 4.2, 2.8, and 1.8 kilobases. All the viral transcripts detected in the VX2 tumor cells were polyadenylated at the same site (position 4367) 20 base pairs beyond the first AATAAA signal which borders the E region.